Effects of Soaking Rice Seeds with Biofertilizers on Brown Spot Disease Drechslera oryzae and Sprout Growth. - Risanti Eka Liasaputri; A. Marthin Kalay; Hanry R. D. Amanupunyo (Agrologia, 2023)
Rice (Oryza sativa L.) is a staple food crop for the majority of the population in Indonesia. In rice cultivation, brown spot disease is often damaged by the fungus Drechslera oryzae. This study aims to examine the effect of applying biofertilizers on brown spot disease and growth of rice sprouts. The treatments tried were Bion-up, KIBRT, Azoto-Tricho, biofertilizers and propineb fungicide as a comparison. The experimental design used a completely randomized design with four replications. The observed variables were disease intensity, shoot height, root length, and fresh weight of sprouts. The results showed that the application of biological fertilizers Bion up, KIBRT and Azoto-Tricho was effective in controlling brown spot disease and increasing growth in shoot height, root length and sprout fresh weight.